Selection In Segregating Population Of Tomato (Solanum Lycopersicum) For Growth, Yield And Virus Resistance - Islam, MS; Ahmad, S; Hoque, MA (Bangladesh Journal of Agricultural Research, 2011)
Nineteen segregating lines of tomato were evaluated at the Horticulture Research Centre of BARI during winter season of 2008-2009 with a view to developing high yielding virus resistant varieties. Wide variation was observed among the lines in respect of number of fruits per plant (13.5-38.3), individual fruit weight (56.8-162.3g), fruit yield per plant (1.28-2.40 kg), and locule number of fruit (2.0-8.5). The highest number of fruits per plant was observed in the line 14-1-1-1-1, but its corresponding individual fruit weight was only 58.4g. The line 15-3-4-2-1 had the highest individual fruit weight (162.3g). The highest fruit yield was recorded from the line 15-3-4-2-1 (81.6 t/ha), which was closely followed by the line 15-1-2-2-1 (79.5 t/ha). Thirteen genotypes were found free from virus infection up to 60 days after transplanting, while the rest had very low (1.4 - 2.8%) virus incidence. Among the entries, considering yield and virus reaction, the lines, 8-1-3-4-1, 8-1-3-1-1, 8-1-3-2-2, 14-1-1-1-1, 15-3-4-2-1, 15- 1-2-2-1 and 15-1- 2-1-2 were selected for further evaluation and recommendation as varieties. Keywords: Segregating population; tomato. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9278 BJAR 2011; 36(3): 507-512